Supercommunicator : explaining the complicated in a digital age - Pietrucha, Frank J. (American Management Association, 2014)
In our increasingly complicated and data-driven world, many new developments are so complex that only experts comprehend their nuances. But what they don't grasp is how to tell the world about them. Communicating technical content to nontechnical listeners has fast become a critical 21st-century skill. Explaining what you do and why it's important drives funding, policy decisions, media exposure, public awareness, and customer adoption. This groundbreaking guide will help anyone to deliver clear, persuasive messages that win hearts, minds, and budgets. Supercommunicator explains how to:? Distill details and data into big ideas? Deliver meaning to audiences? Use storytelling to captivate and educate? Humanize content to make complicated ideas more tangible? Layer harder ideas on top of easier ideas? Strip away complex language, jargon, and acronyms? Use analogies to explain unfamiliar areas? Master new digital modes of expression? And more Enhanced with a wealth of examples--from how the National Academy of Sciences used audience research to improve the way evolution is taught, to how NASA incorporated cutting-edge tools to visualize issues in climatology--this one-of-a-kind book reveals how to make the complex comprehensible, and the dry deeply compelling.